Spotted knifejaw (Oplegnathus punctatus) MyD88: Intracellular localization, signal transduction function and immune responses to bacterial infection. Issue 89 (June 2019) - Liu, Xiaobing; Li, Xuemei; Du, Xinxin; Sun, Minmin; Wang, Xuangang; Li, Wensheng; Zhai, Jieming; Liu, Jinxiang; Yu, Haiyang; Zhang, Quanqi
Abstract: Myeloid differentiation factor 88 (MyD88) links members of the toll-like receptor (TLR) and interleukin-1 receptor (IL-1R) superfamily to the downstream activation of NF-κB as a "bridge" molecular in response to exogenous pathogen, but the function in spotted knifejaw ( Oplegnathus. punctatus ), a commercial fish in China, is still unknown. We present a functional analysis of spotted knifejaw MyD88 (OppMyD88) with a typical death domain (DD) at the N-terminus and a conservative Toll/IL-1R (TIR) domain at the C-terminus and suggest that MyD88 is important for the activation of TLR-mediated NF-κB with the synergy between domains. Subcellular localization showed that OppMyD88 was distributed in the cytoplasm in a condensed form. Tissues expression profiling analysis showed that OppMyD88 ubiquitously expressed in all tested tissues with the highest expression in the liver, as determined by real-time PCR. The expression of OppMyD88 significantly upregulated in the liver, spleen, kidney and gills within 120 h post Vibrio anguillarum infection. Moreover, we further confirmed that over-expressed OppMyD88 could also induce apoptosis. These results indicate that OppMyD88 might possess important roles in defense against microbial infection and other biological processes in spotted knifejaw similar to those in mammals, which will deepen our understandings in innate immunity of spotted knifejaw. Highlights: A MyD88 homologue was isolated and characterized from O. punctatus (OppMyD88). The gene structure and protein motifs of OppMyD88 were highly conserved among vertebrate. OppMyD88 could be significantly induced in response to V. anguillarum infection. OppMyD88 located in cytoplasm and can fully activate NF-κB under the joint action of structural domains. OppMyD88 could induce apoptosis of HEK-293T cells relies on its death domain.